Nonverbal Communication - Hayshuk, Yulia; Vlasenko, Ludmila (My University, 2014)
Not all gestures and body language are for positive communication. One example of this is gang symbols. These are nonverbal communications that may tell something about whether or not someone is in a gang or fives in a certain area where some gangs are. For example, the way a person wears their shirt or how a cap is worn (like to the left or right side) may tell others that the person is in a certain gang. The color of their clothes may mean something as well. Another communication that is used by gangs is special hand signs. These signs are used by one person to show another person that they are in a certain gang. These signs can be a threat sign to someone in a different or enemy gang.
Keywords: спілкування; символи; невербальна комунікація; nonverbal Communication; symbols; intercourse; кафедра ділової іноземної мови та міжнародної комунікації